Variable Rate Technology for Florida Citrus - Reza Ehsani; Arnold Schumann; Masoud Salyani (EDIS)
AE444, a 5-page illustrated fact sheet by Reza Ehsani, Arnold Schumann, and Masoud Salyani, describes this important site-specific management component of precision agriculture which provides economic benefits to growers while reducing the application of agrochemicals. Includes references. Published by the UF Department of Agricultural and Biological Engineering, January 2009.